Characteristics of meter-scale surface electrical discharge propagating along water surface at atmospheric pressure. (13th September 2016) - Hoffer, Petr; Sugiyama, Yuki; Hosseini, S Hamid R; Akiyama, Hidenori; Lukes, Petr; Akiyama, Masahiro
Abstract: This paper reports physical characteristics of water surface discharges. Discharges were produced by metal needle-to-water surface geometry, with the needle electrode driven by 47 kV (FWHM) positive voltage pulses of 2 µ s duration. Propagation of discharges along the water surface was confined between glass plates with 2 mm separation. This allowed generation of highly reproducible 634 mm-long plasma filaments. Experiments were performed using different atmospheres: air, N2, and O2, each at atmospheric pressure. Time- and spatially-resolved spectroscopic measurements revealed that early spectra of discharges in air and nitrogen atmospheres were dominated by N2 2nd positive system. N2 radiation disappeared after approx. 150 ns, replaced by emissions from atomic hydrogen. Spectra of discharges in O2 atmosphere were dominated by emissions from atomic oxygen. Time- and spatially-resolved emission spectra were used to determine temperatures in plasma. Atomic hydrogen emissions showed excitation temperature of discharges in air to be about 2  ×  10 4 K. Electron number densities determined by Stark broadening of the hydrogen H β line reached a maximum value of ~10 18 cm −3 just after plasma initiation. Electron number densities and temperatures depended only slightly on distance from needle electrode, indicating formation of high conductivity leader channels. Direct observation of discharges by high speed camera showed that the average leader head propagation speed was 412 km · s −1, which is substantially higher value than that observed in experiments with shorter streamers driven by lower voltages.